PENGARUH DIVIDEND PAYOUT RATIO DAN INFORMASI ARUS KAS TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Maria Yanida; Ni Putu Agustinawati (Politeknik Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of dividend payout ratio and cash flow information on the trading volume of banking companies' shares on the Indonesia Stock Exchange. Secondary data obtained from the website idx.co.id and Phintraco Sekuritas. The results of the study state that the dividend payout ratio partially affects the volume of stock trading, while the cash flow information partially has no effect on the volume of stock trading. Dividend payout ratio and cash flow information simultaneously affect the volume of stock trading with the Adjusted R Square coefficient of 0.223 which means only 22.3% of the stock trading volume variable can be explained by the dividend payout ratio variable and operating cash flow information, whereas the remaining 77.7% is explained by other factors not included in this regression analysis.